Modified C9 petroleum resin for toughening epoxy resin and preparation method thereof
The modified carbon nine petroleum resin is formed by copolymerizing polyanhydride, active silicone monomer, and highly active diene with the ethylene cracking by-product carbon nine fraction, which solves the brittleness and compatibility problems of epoxy resin and petroleum resin. , achieving higher toughness, heat resistance and adhesion, avoiding odor deterioration.
Patent Information
- Application Number
- CN202411442776.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-17
AI Technical Summary
The existing epoxy resins and petroleum resins have high brittleness and poor impact resistance after curing. The modification method has problems such as poor compatibility, high cost, poor toughening effect and odor deterioration, making it difficult to comprehensively improve toughness and adhesion.
Modified segments are prepared by copolymerizing polyanhydrides, activated siloxane monomers and highly active diene, and polymerized with the ethylene cracking by-product Carbon Nine fraction to form modified Carbon Nine petroleum resin, which is improved through the heat-induced polymerization and stripping process. The polarity and crosslinking ability of the resin.
Improve the toughness and heat resistance of epoxy resin, enhance the compatibility and cross-linking ability with epoxy resin, improve the adhesion and service life of the resin, avoid odor deterioration problems, and achieve better toughening and heat resistance.
Smart Images

Figure CN119320475A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of petroleum resins, and particularly relates to a modified carbon nine petroleum resin for toughening epoxy resin and a preparation method thereof. Background Art
[0002] Epoxy resin is an important and common thermosetting resin with a regular molecular structure. After being cured by curing agents such as aliphatic amines, alicyclic amines, aromatic amines, polyamides, acid anhydrides, resins, and tertiary amines, it forms a high-strength polymer with stable performance and uniform structure. However, during the curing process, the molecular structure is highly cross-linked into a three-dimensional network structure, and the molecular chains are not easy to slide, resulting in the cured resin having the characteristics of high brittleness and poor impact resistance, which limits the application of epoxy resin in many industries. In order to improve the practical application performance of epoxy resin, the epoxy resin industry has done a lot of work mainly on the toughening modification of epoxy resin. The earliest use of liquid polysulfide rubber, nitrile rubber, etc. For example, patent CN103374320A proposed a method for toughening epoxy resin with modified nitrile rubber. Since such methods reduce the glass transition temperature and heat resistance and other properties too much and some methods increase the curing time, the disadvantages are still relatively large. Later, the industry successively proposed thermoplastic resins, thermotropic liquid crystal polymers, rigid particles, core-shell polymer particles, electrospinning technology nanofibers, and polysiloxanes with high attention to toughen epoxy resins. The above materials all have different toughening effects. For example, patent CN106476365A mentioned that epoxy resin substrates and glass fibers are alternately coated or laid in sequence to obtain toughened epoxy resin-based glass fiber composite materials, and the final impact strength is increased by 17-35%. However, such methods also encounter the problem of poor compatibility with epoxy resins, and there is a certain difficulty in mixing evenly with epoxy resins. They can only have a toughening effect in a local or fixed direction, and cannot comprehensively improve the toughness of epoxy resins.
[0003] At the same time, in the paint industry, alkyd resin is usually used as the base resin for curing. With the development of the industry, higher requirements are placed on the drying speed, anti-cracking and glossiness of the paint film. Paint manufacturers will use the method of adding petroleum resin for modification to improve the drying speed and glossiness of the paint film. However, petroleum resin products have poor polarity. On the one hand, they have poor compatibility with alkyd resin, which affects the glossiness of the paint film after drying. After the paint film dries, white spots and other problems that affect the appearance will appear. In addition, alkyd resin also has poor toughness after curing, and the paint film surface is prone to cracking. On the other hand, the adhesion to polar materials such as wood, gravel roads, and metal products is low, and the requirements of long-term high adhesion cannot be met. In order to improve the polarity of petroleum resin, the industry has also conducted a series of modified grafting studies. For example, patent CN 112661905A mentioned that after mixing C9 fraction, inert solvent and maleic anhydride, a strong acid catalyst was added dropwise in an inert gas atmosphere. After a period of polymerization, a terminator was added, washed with water, and distilled to obtain maleic anhydride-modified carbon nine petroleum resin. The resin has good compatibility, improved resin viscosity, increased resin adhesion, good toughness and stability, and improved performance. Another example is patent CN1298802C mentioned that petroleum resin and maleic anhydride are mixed and added to a reactor, and then xylene solvent is added to reflux, the temperature is raised to dissolve the petroleum resin and maleic anhydride, benzoyl peroxide and polybutadiene are added, and the xylene solvent is evaporated after the reaction is completed. Then, ethylene-vinyl acetate copolymer and styrene-butadiene rubber or butyl acrylate paraffin and calcium carbonate are added and stirred to obtain a hot melt adhesive suitable for road construction. Another example is the patent CN102153710A, which mentions that maleic anhydride is grafted onto petroleum resin under the action of an initiator and applied to wood-plastic composite materials to obtain composite materials with excellent performance. However, the modification of the above products is costly and has poor toughening effect. The resin and the matrix resin are physically mixed and cannot undergo cross-linking reaction. On the other hand, new problems will arise. For example, the removal of unreacted maleic anhydride requires washing, stripping and other processes, and the post-processing process is complicated. The residual maleic anhydride at the ppm level will also cause serious odor deterioration problems. The grafted product has poor stability and pungent odor, and cannot be commercialized. For another example, patent CN106574024B mentions the use of silane and monomers, wherein the monomers include cycloolefins having at least one olefinic unsaturated group selected from the C5 fraction, C9 fraction and dicyclopentadiene of naphtha cracking, so that petroleum resin as a thermoplastic resin can be used as a reactive adhesive, and ultimately an eco-friendly reactive adhesive can be provided. However, the silane-modified petroleum resin obtained by this method has a low grafting rate, resulting in a long curing time of the adhesive and a long curing reaction cycle. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a modified carbon nine petroleum resin for toughening epoxy resin and a preparation method thereof, which solves the problems of the demand for toughening and volume-increasing effects of epoxy resin or alkyd resin and the utilization rate of polyanhydride in the methyltetrahydrophthalic anhydride industry.
[0005] The invention provides a modified C9 petroleum resin for toughening epoxy resin. The modified segment is prepared by copolymerizing a polyanhydride, an active siloxane monomer and a high-activity diene, and then polymerized with a C9 fraction of an ethylene cracking byproduct to prepare the modified C9 petroleum resin.
[0006] The source of the polymeric anhydride described in the present invention is: the production process of methyltetrahydrophthalic anhydride is that the carbon penta diene and maleic anhydride undergo Diels-Alder diene synthesis reaction under heat-induced conditions to generate methyltetrahydrophthalic anhydride, and methyltetrahydrophthalic anhydride undergoes isomerization reaction with strong acid catalysts such as polyphosphoric acid at high temperature. During the isomerization reaction, part of the methyltetrahydrophthalic anhydride undergoes self-polymerization to generate a by-product polymeric anhydride. The molecular weight difference between this substance and methyltetrahydrophthalic anhydride is large, and the boiling point difference is large. After the isomerization is completed, the finished product methyltetrahydrophthalic anhydride is extracted from the top by vacuum distillation, and the by-product polymeric anhydride is extracted from the bottom. The polymeric anhydride contains more polar groups such as hydroxyl groups, anhydride groups, etc., and the acid value reaches more than 200mgKOH / g. After polymerization, the product softening point is 50-120℃, the color is bright, the chain end contains double bonds, and copolymerization reaction can occur. The process of methyltetrahydrophthalic anhydride generating polymeric anhydride is as follows;
[0007]
[0008] Preferably, the reactive siloxane monomer is one or more of tetramethyltetravinylcyclotetrasiloxane, methylvinyldimethoxysilane, vinyltriethoxysilane, 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane, and 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane. More preferably, the reactive siloxane monomer is tetramethyltetravinylcyclotetrasiloxane.
[0009] Preferably, the high-activity diene is a C4-C9 diene.
[0010] More preferably, the C4-C9 diene is one or more of butadiene, piperylene, isoprene, cyclopentadiene, methylcyclopentadiene, vinyl norbornene, ethylidene norbornene, norbornene, and dicyclopentadiene. Most preferably, the C4-C9 diene is one or more of piperylene, isoprene, and vinyl norbornene. The highly active diene can be mixed with an inert solvent in advance to form a solution, and the concentration of the highly active diene is controlled to be 10-50wt%, preferably 20-40wt%, and the inert solvent is a component without active groups, such as pure products or mixtures of cyclohexane, toluene, xylene, trimethylbenzene, methylcyclohexane, ethylcyclohexane, etc.
[0011] Preferably, the carbon nine fraction of the ethylene cracking byproduct contains 0-2% of cyclopentadiene, 2-10% of styrene, 10-25% of methylstyrene, 10-30% of dicyclopentadiene, 5-20% of indene, 2-10% of methylindene, 5-15% of methyldicyclopentadiene, 1-5% of naphthalene and other inert components not containing unsaturated bonds, such as pure products or mixtures of cyclohexane, toluene, xylene, trimethylbenzene, methylcyclohexane, ethylcyclohexane, etc., with typical indicators as follows:
[0012]
[0013] The present invention also provides a method for preparing a modified carbon nine petroleum resin for toughening epoxy resin, comprising the following steps:
[0014] (1) adding a polyanhydride into a first synthesis reactor, adding a highly active diene after heating to obtain a binary copolymer containing a flexible chain segment, and transferring the copolymer to a second synthesis reactor after heat preservation;
[0015] (2) adding active siloxane monomer to the second synthesis reactor, heating the reactor to react, obtaining a silane-modified copolymer, and transferring the copolymer to the third synthesis reactor after heat preservation;
[0016] (3) adding the carbon nine fraction of the ethylene cracking byproduct into the third synthesis reactor, heating the reaction, and then transferring the material to a flash tower for solvent removal, stripping the unreacted solvent monomers at the top of the tower, and the bottom material of the tower entering a stripping tower;
[0017] (4) The bottom material obtained in step (3) is heated by a feed heater and then conveyed to a stripping tower. Methane gas is introduced into the stripping tower for stripping. Methane gas and oligomers are extracted from the top of the tower, and molten modified carbon nine petroleum resin is extracted from the bottom of the tower. The modified carbon nine petroleum resin for toughening epoxy resin is obtained by granulation.
[0018] Preferably, the amount of the polyanhydride added accounts for 3-15% of the mass of the carbon nine fraction of the ethylene cracking by-product, preferably 5-10%; the amount of the high-activity diene added accounts for 20-60% of the mass of the carbon nine fraction of the ethylene cracking by-product, preferably 20-40%; the amount of the active siloxane monomer added accounts for 1-8% of the mass of the carbon nine fraction of the ethylene cracking by-product, preferably 2-5%.
[0019] Preferably, the temperature of the first synthesis reactor in step (1) is set to 180-230°C, preferably 200-220°C.
[0020] Preferably, the dripping time of the high-activity diene in step (1) is between 0.5 h and 5 h, preferably 1-3 h.
[0021] Preferably, the insulation temperature in step (1) is 180-270° C., preferably 210-250° C., and the insulation time is 2-15 h, preferably 5-10 h.
[0022] Preferably, the temperature of the second synthesis reactor in step (2) is set to 200-240° C., preferably 210-230° C., and the reaction time is 5-15 h, preferably 8-12 h.
[0023] Preferably, the temperature of the third synthesis reactor in step (3) is set to 200-260° C., preferably 220-240° C., and the reaction time is 5-20 h, preferably 10-15 h.
[0024] Preferably, the flash tower flash temperature in step (3) is 180-230°C, preferably 200-220°C, and the flash pressure is 150KPa. A small amount of unreacted monomer and solvent mixture is extracted from the top of the flash tower, and this material can be directly used as a diluent solvent for high-activity dienes.
[0025] Preferably, the material temperature of the stripping tower in step (4) is controlled at 200-250°C, preferably 220-240°C, and the methane flow rate is 200-500m 3 / h, preferably 300-400m 3 / h.
[0026] The present invention uses low-value byproducts of methyltetrahydrophthalic anhydride industry, polyanhydride, active siloxane monomers, and highly active dienes to heat-initiate polymerization with carbon nine fractions of ethylene cracking byproducts to obtain modified carbon nine petroleum resin. The modified resin uses active siloxane, active diene, and polyanhydride to obtain a ternary block copolymer through different feeding sequences. The active diene segment is a flexible structure located at the center of the copolymer, providing toughening groups for the modified resin. The double bonds remaining in the active siloxane monomer and polyanhydride enable the copolymer to copolymerize with dicyclopentadiene, styrene, etc. in the carbon nine fractions of ethylene cracking byproducts, and graft to the petroleum resin molecules. In the application process of the petroleum resin, since the petroleum resin carries a polyanhydride group, the group can form a crosslink with the epoxy resin and participate in the curing process of the epoxy resin, so that the crosslinked product has a stronger structural stability, can reduce the influence of the heat resistance and glass transition temperature reduction caused by the low Tg resin entering the epoxy resin system, and can ensure that the heat resistance and glass transition temperature of the crosslinked product are basically unchanged while achieving a toughening effect.
[0027] At the same time, the present invention introduces methyltetrahydrophthalic anhydride oligomer polyanhydride into the modification system, and the chain segment of the polymer still has the cross-linking effect with the epoxy resin, providing curing cross-linking ability during the curing of the epoxy resin, so that the miscibility of the resin of the present invention with the epoxy resin is improved. At the same time, the present invention introduces siloxane groups to increase the polarity of the resin of the present invention, and reacts with the non-polar filler during the curing of the epoxy resin, so that the modified resin of the present invention is connected to the epoxy resin and the filler through chemical bonds. Under the condition of ensuring uniform dispersion of each phase, the cohesion of the epoxy resin and alkyd resin in the final use scenarios, such as road surfaces, wood surfaces, metal surfaces and other construction areas with strong polarity is improved, and cracking, deformation and other problems are not easy to occur, and the adhesion is significantly improved, thereby increasing the service life of the final product.
[0028] Beneficial Effects
[0029] The present invention splits the mixed polymerization reaction and reduces the generation of explosive polymers by step-by-step synthesis while ensuring the copolymerization efficiency. In the early stage of synthesis, since the polyanhydride is a oligomer produced by self-polymerization of raw materials such as methyltetrahydrophthalic anhydride, the product molecular weight is slightly large and the polymerization activity is slightly poor. Therefore, in the early stage of the reaction, a diene with higher activity is added to provide high polymerization activity. The diene with higher activity undergoes chain extension reaction through thermal initiation or catalytic initiation to form flexible molecular segments. The binary polymer segments are then ternary copolymerized with active siloxane monomers through thermal initiation or catalytic initiation to expand the molecular weight to form a ternary block oligomer formed of polyanhydride, olefin segments, and siloxane segments. The block oligomer is then copolymerized with the carbon nine fraction, a byproduct of ethylene cracking, to form a carbon nine resin main molecular chain, and then polymerized. The material is then kept at high temperature for a long time to provide sufficient time for the copolymerization process, thereby improving the degree of polymerization and the polymerization yield. The ternary block oligomer can be copolymerized with the cracked carbon nine as much as possible, and then the unreacted monomers and solvents are removed by flash evaporation, methane stripping, etc. (steam stripping can be used in the laboratory). Then, a carbon nine petroleum resin modified with a polyanhydride and an active siloxane monomer can be obtained. The resin has strong polarity and good compatibility with polar matrix resins such as epoxy resin and alkyd resin. At the same time, it contains polyanhydride carbonyl groups that can be cured with epoxy resin, can undergo cross-linking reaction with the matrix epoxy resin, adjust the curing time of the epoxy resin, and has good volume expansion and toughening effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the preparation device of the present invention; wherein 1 is the carbon nine fraction of the by-product of ethylene cracking; 2 is the polyanhydride; 3 is the active siloxane monomer; 4 is the high-activity diene; 5 is the first synthesis reactor; 6 is the second synthesis reactor; 7 is the third synthesis reactor; 8 is the flash tower; and 9 is the stripping tower. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0032] In order to accurately reflect the characteristics of the product of the present invention, the product was mixed with epoxy resin E-51, curing agent methyltetrahydrophthalic anhydride, accelerator, etc., heated and cured, and prepared into epoxy resin finished products. The performance tests such as impact strength, tensile strength, and glass transition temperature were carried out, and the molecular weight, softening point, and chromaticity of each product in the example were characterized. The detailed information is as follows:
[0033] Epoxy resin E-51: Sinopec;
[0034] Curing agent: methyltetrahydrophthalic anhydride;
[0035] Accelerator: N,N-dimethylbenzylamine, curing method: heating at 80℃ for 30min→heating at 100℃ for 1h→heating at 130℃ for 3h; filler: calcium powder / calcium carbonate;
[0036] Impact strength test standard: GB / T1043.1-2008;
[0037] Tensile strength test standard: GB / T2567-2008;
[0038] Glass transition temperature test method: DSC, German Netzsch D214;
[0039] Molecular weight test method: GPC, Agilent LC;
[0040] Softening point test standard: ASTME28;
[0041] Chromaticity test standard: ASTMD6166.
[0042] Comparative Example 1
[0043] Epoxy resin, curing agent and accelerator are selected and mixed in proportion, then cured and shaped, and then the performance is tested as Comparative Example 1.
[0044] Comparative Example 2
[0045] A thermal polycarbonate nine petroleum resin product PR-110-11 produced by Henghe Materials Technology Co., Ltd. was selected and mixed with epoxy resin, curing agent and accelerator in proportion, and then cured and shaped, and then the performance was tested, as Comparative Example 2.
[0046] Example 1
[0047] 60 g of polyanhydride was added to the first synthesis kettle, the temperature of the first synthesis kettle was raised to 230° C., and then 667 g of a 30% isoprene solution was gradually added dropwise to the first synthesis kettle. After maintaining the temperature at 230° C. for 3 hours, the material was extracted into the second synthesis kettle through the extraction pump. Circulating water was introduced into the coil of the second synthesis kettle to reduce the temperature to 210° C. The temperature in the kettle was maintained, and 80 g of tetramethyltetravinylcyclotetrasiloxane was added three times. After the addition of the material was completed, the second synthesis kettle was heated for 10 hours. After the insulation was completed, the material was extracted into the third synthesis kettle through the extraction pump for heating to 220° C. and the feed pump was used for 3 1 kg of carbon nine fraction, a by-product of ethylene cracking, was added within 10 minutes. After the addition was completed, the temperature in the kettle was maintained at 220°C for insulation for 12 hours. After the insulation was completed, the material was taken out from the third synthesis kettle and sent to a flash evaporator (the device was a flash tower) at normal pressure of 200°C to remove the micro-reactive monomers and inert solvents (this solvent can be recycled). The material at the bottom of the flash evaporator was steam stripped at 220°C. After the stripping was completed, a modified carbon nine resin product was obtained. The resin product was tested for softening point, molecular weight, and color. The product was then mixed with epoxy resin, curing agent, and accelerator, and then heated for curing and shaping. Finally, the cured product was tested for performance.
[0048] Example 2
[0049] 120 g of polyanhydride was added to the first synthesis kettle, the temperature of the first synthesis kettle was raised to 230° C., and then 667 g of a 30% isoprene solution was gradually added dropwise to the first synthesis kettle. After maintaining the temperature at 230° C. for 3 hours, the material was extracted into the second synthesis kettle through the extraction pump. Circulating water was introduced into the coil of the second synthesis kettle to reduce the temperature to 210° C. The temperature in the kettle was maintained, and 80 g of tetramethyltetravinylcyclotetrasiloxane was added three times. After the addition of the material was completed, the second synthesis kettle was heated for 10 hours. After the insulation was completed, the material was extracted into the third synthesis kettle through the extraction pump for heating to 220° C. The feed pump was used to heat the reactor for 3 hours. 1 kg of carbon nine fraction, a by-product of ethylene cracking, was added within 10 minutes. After the addition was completed, the temperature in the kettle was maintained at 220°C for insulation for 12 hours. After the insulation was completed, the material was taken out from the third synthesis kettle and sent to a flash evaporator (the device was a flash tower) at normal pressure of 200°C to remove the micro-reactive monomers and inert solvents (this solvent can be recycled). The material at the bottom of the flash evaporator was steam stripped at 220°C. After the stripping was completed, a modified carbon nine resin product was obtained. The resin product was tested for softening point, molecular weight, and color. The product was then mixed with epoxy resin, curing agent, and accelerator, and then heated for curing and shaping. Finally, the cured product was tested for performance.
[0050] Example 3
[0051] 60 g of polyanhydride was added to the first synthesis kettle, the temperature of the first synthesis kettle was raised to 230° C., and then 667 g of 30% isoprene solution was gradually added dropwise to the first synthesis kettle. After maintaining the temperature at 230° C. for 3 hours, the material was extracted into the second synthesis kettle through the extraction pump. Circulating water was introduced into the coil of the second synthesis kettle to reduce the temperature to 210° C. The temperature in the kettle was maintained, and 160 g of tetramethyltetravinylcyclotetrasiloxane was added three times. After the addition of the material was completed, the second synthesis kettle was heated for 10 hours. After the insulation was completed, the material was extracted into the third synthesis kettle through the extraction pump for heating. After the temperature was raised to 220° C., the material was added through the feed pump. Add 1 kg of carbon nine fraction, a by-product of ethylene cracking, within 30 minutes. After the addition is completed, the temperature in the kettle is maintained at 220°C for insulation for 12 hours. After the insulation is completed, the material is taken out from the third synthesis kettle and sent to a flash evaporator (the device is a flash tower) at normal pressure of 200°C to remove the micro-reactive monomers and inert solvents (this solvent can be recycled). The material at the bottom of the flash evaporator is steam stripped at 220°C. After the stripping is completed, a modified carbon nine resin product can be obtained. The resin product is tested for softening point, molecular weight, and color. The product is then mixed with epoxy resin, curing agent, and accelerator, and then heated for curing and shaping. Finally, the cured product is tested for performance.
[0052] Example 4
[0053] 120 g of polyanhydride was added to the first synthesis kettle, the temperature of the first synthesis kettle was raised to 230° C., and then 667 g of 30% isoprene solution was gradually added to the first synthesis kettle. After maintaining the temperature at 230° C. for 3 hours, the material was taken out by a take-out pump to the second synthesis kettle. The temperature of the second synthesis kettle was controlled at 230° C., and 160 g of tetramethyltetravinylcyclotetrasiloxane was added three times. After the addition of the material was completed, the second synthesis kettle was kept warm for 10 hours. After the insulation was completed, the material was taken out by a take-out pump to the third synthesis kettle. The temperature was controlled at 230° C., and ethylene was added within 30 minutes by a feed pump. 1 kg of the cracking by-product carbon nine fraction was added. After the addition, the temperature in the kettle was kept at 230°C for 12 hours. After the insulation, the material was taken out from the third synthesis kettle and sent to a flash evaporator (the device is a flash tower) at normal pressure of 200°C to remove the micro-reactive monomers and inert solvents (this solvent can be recycled). The material at the bottom of the flash evaporator was steam stripped at 220°C. After the stripping, the modified carbon nine resin product was obtained. The resin product was tested for softening point, molecular weight and color. The product was then mixed with epoxy resin, curing agent and accelerator, heated for curing and shaping, and finally the cured product was tested for performance.
[0054] Example 5
[0055] 120 g of polyanhydride was added to the first synthesis kettle, the temperature of the first synthesis kettle was raised to 230° C., and then 667 g of isoprene solution with a concentration of 40% was gradually added dropwise to the first synthesis kettle. After maintaining the temperature at 230° C. for 3 hours, the material was taken out to the second synthesis kettle through the extraction pump. The temperature of the second synthesis kettle was controlled at 230° C., and 160 g of tetramethyltetravinylcyclotetrasiloxane was added three times. After the addition of the material was completed, the second synthesis kettle was kept warm for 10 hours. After the insulation was completed, the material was taken out to the third synthesis kettle through the extraction pump and the temperature was controlled at 230° C. Ethylene was added within 30 minutes through the feed pump. 1 kg of the cracking by-product carbon nine fraction was added. After the addition, the temperature in the kettle was kept at 230°C for 12 hours. After the insulation, the material was taken out from the third synthesis kettle and sent to a flash evaporator (the device is a flash tower) at normal pressure of 200°C to remove the micro-reactive monomers and inert solvents (this solvent can be recycled). The material at the bottom of the flash evaporator was steam stripped at 220°C. After the stripping, the modified carbon nine resin product was obtained. The resin product was tested for softening point, molecular weight and color. The product was then mixed with epoxy resin, curing agent and accelerator, heated for curing and shaping, and finally the cured product was tested for performance.
[0056] Example 6
[0057] 120 g of polyanhydride was added to the first synthesis kettle, the temperature of the first synthesis kettle was raised to 230° C., and then 667 g of 40% ethylidene norbornene solution was gradually added to the first synthesis kettle. After maintaining the temperature at 230° C. for 3 hours, the material was extracted into the second synthesis kettle through the extraction pump. The temperature of the second synthesis kettle was controlled at 230° C., and 160 g of tetramethyltetravinylcyclotetrasiloxane was added three times. After the addition of the material was completed, the second synthesis kettle was heated for 10 hours. After the end of the insulation, the material was extracted into the third synthesis kettle through the extraction pump and the temperature was controlled at 230° C. The ethylidene norbornene solution was added into the third synthesis kettle through the feed pump within 30 minutes. 1 kg of carbon nine fraction, a by-product of olefin cracking, is added. After the addition is completed, the temperature in the kettle is maintained at 230°C for insulation for 12 hours. After the insulation is completed, the material is taken out from the third synthesis kettle and sent to a flash evaporator (the device is a flash tower) at normal pressure of 200°C to remove the micro-reactive monomers and inert solvents (this solvent can be recycled). The material at the bottom of the flash evaporator is steam stripped at 220°C. After the stripping is completed, a modified carbon nine resin product can be obtained. The resin product is tested for softening point, molecular weight, and color. The product is then mixed with epoxy resin, curing agent, and accelerator, and then heated for curing and shaping. Finally, the cured product is tested for performance.
[0058] Example 7
[0059] 120g of polyanhydride was added to the first synthesis reactor, the temperature of the first synthesis reactor was raised to 230°C, and 667g of 40% methylcyclopentadiene solution was gradually added dropwise to the first synthesis reactor. After maintaining the temperature at 230°C for 3 hours, the material was extracted into the second synthesis reactor through an extraction pump. The temperature of the second synthesis reactor was controlled at 230°C, and 160g of tetramethyltetravinylcyclotetrasiloxane was added three times. After the addition of the material was completed, the second synthesis reactor was heated for 10 hours. After the insulation was completed, the material was extracted into the third synthesis reactor through an extraction pump and the temperature was controlled at 230°C. Ethylene was added into the third synthesis reactor through a feed pump within 30 minutes. 1 kg of carbon nine fraction, a by-product of olefin cracking, is added. After the addition is completed, the temperature in the kettle is maintained at 230°C for insulation for 12 hours. After the insulation is completed, the material is taken out from the third synthesis kettle and sent to a flash evaporator (the device is a flash tower) at normal pressure of 200°C to remove the micro-reactive monomers and inert solvents (this solvent can be recycled). The material at the bottom of the flash evaporator is steam stripped at 220°C. After the stripping is completed, a modified carbon nine resin product can be obtained. The resin product is tested for softening point, molecular weight, and color. The product is then mixed with epoxy resin, curing agent, and accelerator, and then heated for curing and shaping. Finally, the cured product is tested for performance.
[0060] Example 8
[0061] 120 g of polyanhydride was added to the first synthesis kettle, the temperature of the first synthesis kettle was raised to 230° C., and then 667 g of 40% isoprene solution was gradually added to the first synthesis kettle. After maintaining the temperature at 230° C. for 3 hours, the material was extracted into the second synthesis kettle through the extraction pump. The temperature of the second synthesis kettle was controlled at 230° C., and 160 g of methylvinylmethoxysilane was added three times. After the addition of the material, the second synthesis kettle was kept warm for 10 hours. After the insulation was completed, the material was extracted into the third synthesis kettle through the extraction pump and the temperature was controlled at 230° C. The ethylene cracking agent was added within 30 minutes through the feed pump. 1 kg of carbon nine fraction, a by-product of hydrolysis, is added. After the addition is completed, the temperature in the kettle is maintained at 230°C for insulation. The insulation time is 12 hours. After the insulation is completed, the material is taken out from the third synthesis kettle and sent to a flash evaporator (the device is a flash tower) at normal pressure of 200°C to remove the micro-reactive monomers and inert solvents (this solvent can be recycled). The material at the bottom of the flash evaporator is steam stripped at 220°C. After the stripping is completed, a modified carbon nine resin product can be obtained. The resin product is tested for softening point, molecular weight, and color. The product is then mixed with epoxy resin, curing agent, and accelerator, and then heated for curing and shaping. Finally, the cured product is tested for performance.
[0062] Example 9
[0063] 120 g of polyanhydride was added to the first synthesis kettle, the temperature of the first synthesis kettle was raised to 230° C., and then 667 g of 40% isoprene solution was gradually added to the first synthesis kettle. After maintaining the temperature at 230° C. for 3 hours, the material was extracted into the second synthesis kettle through the extraction pump. The temperature of the second synthesis kettle was controlled at 230° C., and 160 g of vinyl triethoxysilane was added three times. After the addition of the material, the second synthesis kettle was kept warm for 10 hours. After the insulation was completed, the material was extracted into the third synthesis kettle through the extraction pump and the temperature was controlled at 230° C., and ethylene was added to the cracking agent within 30 minutes through the feed pump. 1 kg of by-product carbon nine fraction is added. After the addition is completed, the temperature in the kettle is maintained at 230°C for insulation. The insulation time is 12 hours. After the insulation is completed, the material is taken out from the third synthesis kettle and sent to the flash evaporator (the device is a flash tower) at normal pressure of 200°C to remove the micro-reactive monomers and inert solvents (this solvent can be recycled). The material at the bottom of the flash evaporator is steam stripped at 220°C. After the stripping is completed, the modified carbon nine resin product can be obtained. The resin product is tested for softening point, molecular weight, and color. The product is then mixed with epoxy resin, curing agent, and accelerator, and then heated for curing and shaping. Finally, the product is tested for performance after curing.
[0064]
[0065] The above table is a comparison of comparative examples and examples. From the comparison of comparative example 2 and examples 1-6, the softening point and molecular weight of the modified products show an upward trend, which improves the disadvantage that the addition of carbon nine resin affects the heat resistance of epoxy resin. From the analysis of examples 1-5 and comparative example 2, the increase in the amount of polyanhydride added will slightly increase the molecular weight, but has little effect on the softening point. After the increase in the amount of tetramethyl tetravinylcyclotetrasiloxane monomer, the molecular weight of the resin does not change significantly, but the softening point will increase, and after adding two monomers for copolymerization, the color of the resin increases slightly. From the comparison of examples 5-7, it can be seen that the performance of the resin changes greatly after the active diene monomer is replaced. The molecular weight of the modified resin prepared by isoprene increases significantly, the softening point decreases, and the color number decreases. The molecular weight of the modified resin prepared by vinyl norbornene is relatively low, and the molecular weight of the modified resin prepared by methylcyclopentadiene is between the two. The specific reason may be the high steric effect brought by the ring structure of the active monoolefin side chain, which leads to a decrease in the degree of polymerization of the polymer and a decrease in the molecular weight. From the comparison of Examples 6, 8 and 9, it can be seen that changing different siloxane monomers will also have a small impact on the resin molecular weight and softening point.
[0066]
[0067] The above table is a comparison of the application tests of the comparative examples and the examples. From the comparison of comparative examples 1 and 2 with examples 1-6, the modified carbon nine resin does have different degrees of toughening effect, and the glass transition temperature of the resin also changes differently. From comparative examples 1 and 2, ordinary carbon nine resin has a small amount of toughening effect, but the glass transition temperature and tensile strength are reduced to varying degrees. From comparative example 2 and examples 1-5, the toughening effect of the resin is gradually improved after increasing the amount of polyanhydride and tetramethyltetravinylcyclotetrasiloxane, and the glass transition temperature and tensile strength are also increased to varying degrees, indicating that the product effect is gradually improved. From examples 5-7, different types of active dienes have different toughening effects. This is because the chain structure of dienes is more flexible and more stable, but examples 6-7 have better color. If in some application scenarios, the product color is required to be high, and the toughening and temperature resistance are not required to be very high, the use of cyclic active dienes is also a good choice. From the comparison of examples 8 and 9, it can be seen that the toughening effect is also affected to varying degrees after replacing different siloxane monomers.
[0068] In addition, when the resin of the present invention is mixed with an alkyd resin, the compatibility with the alkyd resin is improved due to the increase in polarity. Compared with traditional petroleum resins, no insoluble matter is generated during the production process of paints and other products, and the paint is transparent and bright. At the same time, due to the higher molecular weight than ordinary resins, the cohesive force of the paint is higher. At the same time, the presence of flexible groups makes the paint less likely to crack, deform and other problems. After the paint is applied, the adhesion to the construction areas with strong polarity such as road surfaces, wood surfaces, and metal surfaces will be partially improved, thereby increasing the service life of the paint.
Claims
1. A modified carbon nine petroleum resin for toughening epoxy resin, characterized in that: The modified chain segment is prepared by copolymerizing polyanhydride, active siloxane monomer and high-activity diene, and then polymerized with the carbon nine fraction of ethylene cracking byproduct to prepare the modified carbon nine petroleum resin.
2. The modified C9 petroleum resin according to claim 1, characterized in that: The active siloxane monomer is one or more of tetramethyltetravinylcyclotetrasiloxane, methylvinyldimethoxysilane, vinyltriethoxysilane, 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane, and 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane.
3. The modified C9 petroleum resin according to claim 1, characterized in that: The high-activity diene is a C4-C9 diene.
4. The modified C9 petroleum resin according to claim 3, characterized in that: The C4-C9 diene is one or more of butadiene, piperylene, isoprene, cyclopentadiene, methylcyclopentadiene, vinyl norbornene, ethylidene norbornene, norbornene, and dicyclopentadiene.
5. The modified C9 petroleum resin according to claim 1, characterized in that: The carbon nine fraction of the ethylene cracking byproduct contains 2-8% of cyclopentadiene, 2-10% of styrene, 10-20% of methyl styrene, 10-30% of dicyclopentadiene, 5-20% of indene, 2-10% of methyl indene, and other inert components without unsaturated bonds.
6. A method for preparing a modified C9 petroleum resin for toughening epoxy resin as claimed in any one of claims 1 to 5, comprising the following steps: (1) adding a polyanhydride into a first synthesis reactor, adding a highly active diene after heating to obtain a binary copolymer containing a flexible chain segment, and transferring the copolymer to a second synthesis reactor after heat preservation; (2) adding active siloxane monomer to the second synthesis reactor, heating the reactor to react, obtaining a silane-modified copolymer, and transferring the copolymer to the third synthesis reactor after heat preservation; (3) adding the carbon nine fraction of the ethylene cracking byproduct into the third synthesis reactor, heating the reaction, and then transferring the material to a flash tower for solvent removal, stripping the unreacted solvent monomers at the top of the tower, and the bottom material of the tower entering a stripping tower; (4) The bottom material obtained in step (3) is heated by a feed heater and then conveyed to a stripping tower. Methane gas is introduced into the stripping tower for stripping. Methane gas and oligomers are extracted from the top of the tower, and molten modified carbon nine petroleum resin is extracted from the bottom of the tower. The modified carbon nine petroleum resin for toughening epoxy resin is obtained by granulation.
7. The preparation method according to claim 6, characterized in that: The amount of the polyanhydride added is 3-15% of the mass of the carbon nine fraction of the ethylene cracking byproduct; the amount of the high-activity diene added is 20-60% of the mass of the carbon nine fraction of the ethylene cracking byproduct; The amount of the active siloxane monomer added is 1-8% of the mass of the carbon nine fraction of the ethylene cracking byproduct.
8. The preparation method according to claim 6, characterized in that: The temperature of the first synthesis reactor in step (1) is set to 180-230°C.
9. The preparation method according to claim 6, characterized in that: The temperature of the second synthesis reactor in step (2) is set to 200-240° C., and the reaction time is 5-15 hours.
10. The preparation method according to claim 6, characterized in that: The temperature of the third synthesis reactor in step (3) is set to 200-260° C., and the reaction time is 5-20 h.
Citation Information
Patent Citations
Preparation method of modified petroleum resin
CN102153710A
Method for toughening and curing epoxy resin adhesive by using amino-terminated liquid nitrile rubber
CN103374320A
Toughened epoxy-resin-based glass fiber composite material and preparation method thereof
CN106476365A
Curable petroleum resins and their preparation methods
CN106574024B
Method for preparing heat molten type petroleum resin based adhesive
CN1298802C